In situ fabrication of Al surface plasmon nanoparticles by metal–organic chemical vapor deposition for enhanced performance of AlGaN deep ultraviolet detectors. Issue 5 (17th March 2020) - Wu, You; Sun, Xiaojuan; Shi, Zhiming; Jia, Yuping; Jiang, Ke; Ben, Jianwei; Kai, Cuihong; Wang, Yong; Lü, Wei; Li, Dabing
Abstract : This work realized the in situ fabrication of Al surface plasmon nanoparticles by metal–organic chemical vapor deposition (MOCVD). Abstract : Al nanoparticles (NPs) have been proven to be the efficient choice for plasmon enhanced AlGaN-based ultraviolet (UV) photodetectors. Previous studies have mainly been focused on the ex situ preparation of Al NPs, but the in situ growth of Al NPs is more desired. In this work, we predict the feasibility for in situ growth of Al surface plasmon NPs on AlGaN-based UV photodetectors by first-principles calculations, and realized it experimentally by metal–organic chemical vapor deposition. For metal–semiconductor–metal type AlGaN-based photodetectors with in situ grown Al surface plasmons, the peak of responsivity was at 288 nm, enhanced 9 times more than that without Al NPs at 10 V bias. The in situ growth method of Al NPs in the present work provides an efficient method for improving the performance of AlGaN-based UV photoelectric devices.